Comparison of Volatility of Jakarta Islamic Index with LQ45 Stock in Indonesia - Prasetyo, Alvin; Vibriyanto, Norita; Wulandari, Rini (IPB University, 2024)
This research aims to compare and analyze the volatility of Jakarta Islamic Index shares and LQ45 shares. The methods used are ARMA and ARCH-GARCH. The data used is time series data with the daily period 2020-2024. The unit root test results show that the Jakarta Islamic Index with LQ45 shares is stationary at level or I(0), then the lag for autoregressive is 1, and the lag for moving average is 3. Therefore, the model formed is ARMA. The estimation results show that the volatility of LQ45 shares is higher than that of the Jakarta Islamic Index shares. This means that the LQ45 share price experienced large and rapid fluctuations in a relatively short period compared to the Jakarta Islamic Index share price. This condition is often exploited by short-term traders to gain profits. The contribution of this research is to provide empirical results related to the volatility of conventional shares and sharia shares, so that it can be seen which shares have high risk. The policy recommendation given is that investors must be careful with stocks that have high volatility, but for investors who already understand market conditions it can be an opportunity for profit.